ANALYSIS OF SOCIAL FORESTRY REGULATION SUBSTANCE IN INDONESIA - Arif,Suhaidi,Alyi Syahrin,Runtung Sitepu (International Journal of Advanced Science and Technology, 2020)
Social forestry aims to reduce poverty, unemployment and inequality in management, utilization of forest areas, as well as aiming at resolving tenure and justice issues for local communities, in or around forest areas. The inception of various social forestry regulations as an effort to curb the implementation of social forestry as stipulated in the Minister of Environment and Power Regulation Number P-83 of 2016 concerning Problem Forestry in terms of substance is feasible for analysis with various regulations relating to the objectives of the implementation of social forestry in Indonesia. Through an analysis study of the substance of social forestry regulations it was found that the content in social forestry regulations was not in line with some specific regulations related to poverty alleviation, the holding of local government authority and the policy of determining the parties in forestry partnerships as part of social forestry schemes. Through this research, a recommendation was made to revise the regulations governing social forestry so that harmonization with other sector regulations would be in line with the objectives of social forestry as a suggestion to keep the forest in a sustainable environment and the people in peace.